KUALITAS PRODUK BERPENGARUH POSITIF DAN SIGNIFIKAN TERHADAP KEPUTUSAN PEMBELIAN - Munafis, Subhan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The research was conducted at the LN shop in CV. NB which is located on Jl. Semboja, Kebon Kopi Village, Bogor Tengah District, Bogor City for 6 months with the analytical approach used is quantitative. The population is 130 people. The sample for this research was 99 people. The results of the research show that the t test (Partial Test) on the product quality variable is 1.990 with a sig value of 0.005 and ? = 5%, obtained t table = 1.985 so it can be said that the product quality variable has a positive effect and a significant effect. influence on purchasing decisions at Lazada Nairastore. The service quality variable has a significant value of 2.316 with a sig value of 0.003 and ? = 5%, obtained ttable = 1.985 so it can be concluded that service quality has a positive and significant effect on purchasing decisions at Lazada Nairastore. Meanwhile, simultaneously product quality and service quality have a positive and significant effect on purchasing decisions with the F test results obtained by fcount = 4.710 which is greater than the ftable for ? = 5% of 3.088 and a significant value of 0.011 which is less than 0.05.